Analisis Laporan Keuangan Sebagai Penilaian Kinerja Pt Sido Muncul Tbk Periode 2019-2023 - A. Fajar Mujahidin; Fatkhuri Fatkhuri (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
Sido Muncul Tbk is one of the largest and most modern herbal medicine producers in Indonesia. In conducting its business activities, PT Sido Muncul Tbk certainly requires investors and creditors as sources of funding. For that reason, financial statement analysis is needed as a source of information about the company's financial condition. Based on the financial reports of PT Sido Muncul Tbk for the period from 2019 to 2023, there has been a fluctuating increase, even though Indonesia was hit by the COVID-19 pandemic in 2020 to 2021. The type of research is descriptive quantitative research with data sourced from the financial reports of PT Sido Muncul Tbk as of December 31 from 2019 to 2023. The first result, the assessment of the financial performance of PT Sido Muncul Tbk based on liquidity ratio analysis using the current ratio, shows that the current ratio values from 2019 to 2023 have experienced fluctuating conditions but remain in the very good category, above the industry's minimum standard of 200%. Second, the results of the solvency ratio analysis using the Debt to Asset ratio (DAR) indicate that the DAR values from 2019 to 2023 are in the very good category, as they are below the industry's maximum standard of 35%. Third, the analysis of profitability ratios using the Return on Equity (ROE) shows that the ROE values from 2019 to 2023 have experienced fluctuating conditions but remain below the industry standard of 40%.